2011
DOI: 10.1186/1752-4458-5-23
|View full text |Cite
|
Sign up to set email alerts
|

Using the World Health Organization's 4S-Framework to Strengthen National Strategies, Policies and Services to Address Mental Health Problems in Adolescents in Resource-Constrained Settings

Abstract: BackgroundMost adolescents live in resource-constrained countries and their mental health has been less well recognised than other aspects of their health. The World Health Organization's 4-S Framework provides a structure for national initiatives to improve adolescent health through: gathering and using strategic information; developing evidence-informed policies; scaling up provision and use of health services; and strengthening linkages with other government sectors. The aim of this paper is to discuss how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 46 publications
(63 reference statements)
1
12
0
Order By: Relevance
“…Overall, the prevalence rates reported for sub-Saharan adolescents in this review are high in comparison with studies from European countries and the USA [ 60 – 62 ] and other reviews of adolescent mental health problems in resource-constrained settings [ 5 , 7 , 13 , 63 65 ]. However, reviews by Cortina et al [ 13 ] and Kieling et al [ 5 ] included younger participants aged 0 to 16 years, whereas this review focused on adolescence, a typical age of onset and manifestation of mental health disorders [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the prevalence rates reported for sub-Saharan adolescents in this review are high in comparison with studies from European countries and the USA [ 60 – 62 ] and other reviews of adolescent mental health problems in resource-constrained settings [ 5 , 7 , 13 , 63 65 ]. However, reviews by Cortina et al [ 13 ] and Kieling et al [ 5 ] included younger participants aged 0 to 16 years, whereas this review focused on adolescence, a typical age of onset and manifestation of mental health disorders [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, females are more frequently exposed to risk factors, such as gender discrimination, exposure to violence and sexual abuse, and more frequently affected by internalizing mental health disorders [ 65 , 66 ]. Furthermore, the majority of studies included utilised screening tools, which have been shown to overestimate prevalence rates compared to diagnostic interviews [ 13 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the African context, data on adolescent mental health is scarce and capacities for mental health care are limited, as is the case in many low-income settings (Fisher and Cabral de Mello, 2011 ; Erskine et al ., 2017 ; WHO, 2018 ; UNICEF, 2018c ). Regarding the mental health of HIV-positive adolescents in sub-Saharan Africa, numerous studies have been published in recent years (Kamau et al ., 2012 ; Louw et al ., 2016 ; Lwidiko et al ., 2018 ; Hoare et al ., 2019 ; West et al ., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other health system strengthening strategies which are disease-specific [ 13 ] or narrow [ 14 16 ], the WHO’s health system framework intends to improve the overall health in a responsive, financially fair and most efficient way [ 11 ]. Evidences revealed that the framework helps to assess in-country healthcare performances [ 17 ], interactions between health reforms and country health systems [ 18 ], implications of health sector reforms [ 19 ], and the status of health facilities [ 20 ] and specific health problems [ 21 ].…”
Section: Introductionmentioning
confidence: 99%